Various Extracts of Some Medicinal Plants as Inhibitors for Beta-lactamase Activity (Baghdad Science Journal, 2021)
The inhibitory effect of acetone, ethanol, and aqueous extracts of ten medicinal plants on β-lactamase from Staphylococcus sciuri and Klebsiella pneumoniae was investigated in vitro by starch-iodine agar plate method. The results revealed the success of starch-iodine method for the detection of the inhibition of β-lactamase activity by the various extracts of each individual plant. The acetone extracts of Catharanthus roseus, Eucalyptus camaldulensis, and Schinus terebinthifolius induced an inhibitory effect on β-lactamase from Staphylococcus sciuri. On the other hand, acetone extracts from only Eucalyptus camaldulensis, and Schinus terebinthifolius expressed strong inhibitory effect on β-lactamase from Klebsiella pneumoniae. The acetone extracts expressed the highest inhibition for β-lactamases activity compared to ethanolic and aqueous extracts which exhibited appreciable inhibitory effect. β-lactamase from S. sciuri was inhibited by extracts from C. roseus, E. camaldulensis and S. terebinthifolius whereas β-lactamase from K. pneumoniae was inhibited only by extracts from E. camaldulensis and S. terebinthifolius.